Dimensions of Education, Liberation, and Social Change: A Study of Women's Experiences in Kampung Perca Bogor in Facing Covid-19 - Raji Supriyadi; Elih Sudiapermana; Joni Rahmat Pramudia (CV. Rayyan Dwi Bharata, 2023)
This study aims to determine the dimensions of social change in women's groups, through training and multistakeholder collaboration on the formation of Kampung Perca in Sindangsari Village, Bogor. The women in the City of Rain have shown their participation so that they find ways out of the impact of Covid-19 through the production of creative businesses in the form of patchwork crafts which begin with sewing training. This business is growing and its products are in demand by many people. Plus the collaboration of various actors and parties, such as the Bogor City Government and West Java Province as well as the business world, so that this village in Sindangsari becomes Kampung Perca, a thematic village. Results of this study; First, initiatives and decision-making processes are carried out by the women's own community. Second, ability improvement through training. Third, the approach taken adapts to local conditions, where a lot of fabric waste/waste originating from factories and convection has not been utilized in the Sindangsari area. Fourth, in carrying out community development and empowerment, it is emphasized through a social learning process in which there is collaborative interaction between the bureaucracy and the community starting from the planning process to evaluation by underpinning mutual learning. And, fifth, the establishment of a network process between the bureaucracy and non-governmental organizations, independent traditional organizational units.